The new leader : harnessing the power of creativity to produce change - Kosiarek, Renee (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Leaders in the 21st-century must learn to solve problems and motivate followers with a combination of creativity, leadership, and effective change. In The New Leader: Harnessing the Power of Creativity to Produce Change, readers will develop an understanding of the relationship between creativity, leadership, and change. They will analyze the creative process, learn how to develop a creative culture, and understand effective leadership styles that promote creativity and change. They will explore training to enhance creativity and leadership, and develop practical ways to create an environment that encourages positive growth. The book offers simple techniques to enhance creativity and leadership immediately, while also pointing to long-term changes that will bring even more success. Stories, reflection questions, and theories are intertwined to help the reader develop sound strategies to lead with enhanced creativity. The book helps an overwhelmed leader learn engaging tools to lead change, while encouraging disengaged leaders to try new methods to revive their leadership and accomplish a motivating vision. In the end, leaders will become more effective, engaging, and transformational by adopting the ideas in the book. They will serve as a model for creativity, create spaces that enhance creative growth, and encourage cultures where employees are free to create positive changes for their organizations.
1. Creativity: the crucial ingredient for success -- 2. Finding and using creativity in your organization -- 3. Strong leadership: the foundations -- 4. The transformational, creative leader -- 5. Cultures that enhance creativity and change -- 6. Collaboration: the key to enhanced creativity -- 7. Creating spaces to enhance engagement and success -- 8. Creativity and leadership training that inspires positive growth -- 9. 10 immediate shifts to become a more creative and effective leader -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on June 12, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Creative ability in business; Leadership; change; creative; creative process; creativity; culture; illumination; leader; leadership; transformational leader; Electronic books